A comparative study of financial performance of banking sector in bangladesh – An application of camels rating system - Nimalathasan, B. (University of Jaffna, 2008)
The Banking sector in Bangladesh is different from the banking as seen in other developed countries. This is one of the Major Service sectors in Bangladesh economy, which divided into four categories of scheduled Banks. These are Nationalized Commercial Banks (NCBs), Government Owned Development Financial Institutions (DFIs), Private Commercial Banks (PCBs), and Foreign Commercial Banks (FCBs). Performance of financial Institution is generally measured by applying quantitative techniques of financial measurement. It is a post – mortem examination techniques of achievement of a bank. Many Studies are conducted in different countries to judge the performance of their banking system. Using different statistical methods such as Data Envelopment Analysis (DEA) and the Stochastic Frontier Approach (SFA). The present Study is initiated a Comparative Study of Financial Performance of Banking Sector in Bangladesh using CAMELS rating system with 6562 Branches of 48 Banks in Bangladesh from Financial year 1999-2006. CAMELS rating system basically quantitative technique, is widely used for measuring performance of banks in Bangladesh. Accordingly CAMELS rating system shows that 3 banks was 01 or Strong, 31 banks were rated 02 or satisfactory, rating of 07 banks was 03 or Fair, 5 banks were rated 4 or Marginal and 2 banks got 05 or unsatisfactorily rating. 1 NCB had unsatisfactorily rating and other 3 NCBs had marginal rating.
Keywords: Financial performance; Banking; CAMELS; Rating system